Evaluation of the association between presenteeism and perceived availability of social support among hospital doctors in Zhejiang, China - Xiaoyu Xi; Qianni Lu; Mengqing Lu; Ailin Xu; Hao Hu; Carolina Oi Lam Ung (BMC, 2020)
Abstract Background This study investigated the association between presenteeism and the perceived availability of social support among hospital doctors in China. Methods A questionnaire was administered by doctors randomly selected from 13 hospital in Hangzhou China using stratified sampling. Logit model was used for data analysis. Results The overall response rate was 88.16%. Among hospital doctors, for each unit increase of the perceived availability of social support, the prevalence of presenteeism was decreased by 8.3% (OR = 0.91, P = 0.000). In particular, if the doctors perceived availability of appraisal support, belonging support and tangible support as sufficient, the act of presenteeism was reduced by 20.2% (OR = 0.806, P = 0.000) 20.4% (OR = 0.803, P = 0.000) and 21.0% (OR = 0.799, P = 0.000) respectively with statistical differences. Conclusion In China, appraisal support, belonging support and tangible support, compared to other social support, had a stronger negative correlation with presenteeism among hospital doctors. The benefits of social support in alleviating doctors' presenteeism warrant further investigation.